2014
DOI: 10.5902/198346597084
|View full text |Cite
|
Sign up to set email alerts
|

Investigando o fenômeno de compras coletivas on-line: fatores que influenciam a intensidade das compras

Abstract: A compra coletiva on-line surgiu no Brasil há cerca de dois anos. Tem como objetivo vender produtos e serviços em massa com grandes descontos, exigindo um número mínimo de consumidores para atingir o volume pré-estipulado. Nesse contexto, este estudo visou investigar a relação entre a intensidade de compra coletiva on-line e o interesse do consumidor, a compra por impulso e a insegurança em relação ao site. A coleta dos dados, que englobou 143 respondentes, ocorreu por meio de um questionário contendo questões… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…The literature survey showed that the primary variable that influences online purchasing is price (Andrade & Silva, 2017;Ferreira et al, 2018;Teixeira Filho et al, 2020;Lessa et al, 2021;Comin et al, 2014;Ramayah et al, 2018;Vieira, 2019;Chawla & Kumar, 2022;Quarto et al, 2021;Vieira et al, 2020;Costa, 2021;Silva & Napiri, 2020;Mendonça, 2022;Lara-Jiménez et al, 2021;Brandão, 2018.). One of the differences and main attractions of online stores compared to conventional stores is the prices offered, which are cheaper to buy online than in physical stores.…”
Section: Variables That Influence Online Purchasingmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature survey showed that the primary variable that influences online purchasing is price (Andrade & Silva, 2017;Ferreira et al, 2018;Teixeira Filho et al, 2020;Lessa et al, 2021;Comin et al, 2014;Ramayah et al, 2018;Vieira, 2019;Chawla & Kumar, 2022;Quarto et al, 2021;Vieira et al, 2020;Costa, 2021;Silva & Napiri, 2020;Mendonça, 2022;Lara-Jiménez et al, 2021;Brandão, 2018.). One of the differences and main attractions of online stores compared to conventional stores is the prices offered, which are cheaper to buy online than in physical stores.…”
Section: Variables That Influence Online Purchasingmentioning
confidence: 99%
“…Determinant factors Andrade & Silva, 2017;Ferreira et al, 2018;Teixeira Filho et al, 2020;Lessa et al, 2021;Comin et al, 2014;Ramayah et al, 2018;Vieira, 2019;Chawla & Kumar, 2022;Quarto et al, 2021;Vieira et al, 2020;Costa, 2021;Silva & Napiri, 2020;Mendonça, 2022;Lara-Jiménez et al, 2021;Brandão, 2018. Price Andrade & Silva, 2017;Ferreira et al, 2018;Comin et al, 2014;Abreu et al, 2022;Costa, 2021;Silva & Napiri, 2020;Mendonça, 2022;Brandão, 2018.…”
Section: Referencesmentioning
confidence: 99%
See 1 more Smart Citation